Tourism Development and People of Marginal Livelihood in Khaptad National Park Area, Nepal: Opportunities and Challenges - Poudel, Padma Chandra (Himalayan Review, 2009)
No Abstract or Full Text available The Himalayan Review 35-36 (2004-2005) 19-24